Design and Construction of a Mini Weather Station Based on Telemetry: English - Wulandari, Rindi (Electrical Engineering Departement, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Today, the weather is difficult to predict, so we need a weather observation tool that can provide weather information quickly. AWS (Automatic Weather Station) is an automatic type of traditional weather station, to save manpower or to take measurements from remote areas. AWS real time is an AWS system that can present information in real time to users accompanied by several other features such as warning alarms. Based on the background above, a telemetry-based mini weather station system was created in the form of a model, using the Arduino ATmega2860 Microcontroller as data collector and data processor, the BME Module as a temperature, pressure and humidity sensor, the RTC DS3231 is used as a time and date generator, and SIM 800l as a remote control application. The research conducted includes applied research, with experimental research methods. Testing the tool in the form of taking the average data of the 10th minute and 30th minute. Data is sent via the SIM800l module using the prime sim card which has been filled with an SMS package, with an estimated delivery time of around -10 seconds.